Rare Late Mandibular Metastasis in Follicular Variant of Papillary Carcinoma Thyroid: 'Resurgence of the Sleeping Tumour' - Kanchan P Dholam; Gurkaran Preet Singh; Sandeep V Gurav; Bharat Bharat Rekhi (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Cancer of the thyroid gland is the most common endocrine malignancy constituting for less than 1% of all reported human cancers 1. The propensity of occurrence of thyroid carcinomas is two to four times more in females as compared to males with a median age at diagnosis being 45-50 years [1,2]. Papillary thyroid carcinoma (PTC) is the most common histological type of thyroid cancer and accounts for more than 80 % of thyroid malignancies. Classical PTC (cPTC) is the most common (80%) sub-type of papillary thyroid carcinoma followed by follicular variant (FVPTC) which is found in 9-22.5% of patients [3].